Advokasi Sosial terhadap Perempuan Korban Kekerasan Seksual di P2TP2A Kota Tangerang Selatan - Savira Ratna Ananda; Moh. Amin Tohari (Journal of Creative Student Research, 2023)
Sexual violence that occurs against women can cause deep trauma for the victims who experience it. Victims tend to feel afraid when meeting other people, especially the opposite sex. Cases of sexual violence against women that occurred in South Tangerang City alone experienced an increase of 75% from the previous year. Therefore, there is a great need for a social advocacy process carried out by social service institutions such as P2TP2A. The aim of this research is to find out how the social advocacy process is carried out by P2TP2A South Tangerang City towards women victims of sexual violence. This research method uses descriptive qualitative through interviews, observation and documentation. The research results show that the social advocacy process carried out by P2TP2A South Tangerang City towards women consists of identifying problems, formulating solutions, building political awareness and desire, implementing policies and evaluating.